Using REACH for the EU Environmental Footprint: Building a Usable Ecotoxicity Database, Part I. (14th August 2019) - Saouter, Erwan; Biganzoli, Fabrizio; Pant, Rana; Sala, Serenella; Versteeg, Donald
ABSTRACT: The European Union Environmental Footprint (EU‐EF) is a harmonized method to measure and communicate the life cycle environmental performance of products and organizations. Among 16 different impact categories included in the EU‐EF, 1 focuses on the impact of substances on freshwater ecosystems and requires the use of toxicity data. This paper evaluates the use of the aquatic toxicity data submitted to the EU Registration, Evaluation, Authorisation and Restriction of Chemicals (REACH) regulation. It presents an automated computerized approach for selecting substance ecotoxicity values, building on a set of quality and reliability criteria to extract the most relevant data points for calculating the substance specific hazard values. A selected set of criteria led to the exclusion of approximately 82% of the original REACH ecotoxicological data available as of May 2015 due to incomplete initial encoding of the data by the REACH registrant, missing information such as duration of exposure, endpoint measured, species tested, and imprecise toxicity values (i.e., reported with greater than or less than signs). From an initial set of 305 068 ecotoxicity data records available in the REACH database, the final usable database contains 54 353 toxicity records (29 421 characterized as acute and 24 941 as chronic) covering 9 taxonomic groups, with algae, crustaceans, and fish representing 93% of the data. This data set is valuable for assessing the environmental toxicity of the substance contained whether through traditional substance risk assessment, product toxicity labeling, life cycle assessment (LCA) or environmental impact assessment approaches. However, the resulting loss of approximately 82% of the data suggests that changes in procedures used to generate, report, and document the data within REACH are needed to improve data utility for the various assessment approaches. The rules used to select the data to be used are the primary focus of this article. Integr Environ Assess Manag 2019;15:783–795. © 2019 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC). Key Points: The use European Union Registration, Evaluation, Authorisation and Restriction of Chemicals regulation (REACH) ecotoxicological database has permitted to calculate unique hazard value for >6000 substances. The use of R programming has allowed a transparent and reproducible selection of the data (R codes are provided). About 83% of the ecotoxicological data registered in REACH were excluded for the final estimation of chemical hazard value. A significant number of chemicals (about 23%) have fewer than 2 taxonomic groups from which toxicity data are available.